Clinical use of tobramycin inhalation solution (TOBI®) shows sustained improvement in FEV1 in cystic fibrosis. Issue 6 (9th September 2013) - Konstan, Michael W.; Wagener, Jeffrey S.; Pasta, David J.; Millar, Stefanie J.; Morgan, Wayne J.
Summary Objectives Tobramycin inhalation solution (TIS; TOBI®) has improved forced expiratory volume in 1 sec (FEV1) in cystic fibrosis (CF) trials. Using data from the Epidemiologic Study of CF (ESCF), we assessed the change in level and trend of FEV1 % predicted (pred) over a 2‐year period associated with initiation of TIS during routine clinical practice. Methods Patients age 8–38 years and in ESCF for ≥2 years before treatment with TIS as a chronic therapy were selected if they remained on therapy for 2 years, defined as being on TIS for at least 3 months per year (C‐TIS group). Comparator intervals age 8–38 years used TIS <10% of the time. For each interval, we estimated the level and trend (rate of decline) in FEV1 % pred before and after the index using a piecewise linear mixed‐effects model adjusted for potential confounders. Results During the 2‐year pre‐index period the C‐TIS group (n = 2, 534) had a more rapid decline in FEV1 (−2.49% vs. −1.39% pred/year) and a lower FEV1 at index (62.6% vs. 74.7% pred) than the comparator group (N = 17, 656 intervals). After starting chronic TIS, the FEV1 trend line over the 2‐year post‐index period was higher, but the comparator group's FEV1 was essentially unchanged (difference 2.22, P < 0.001). Change in slope was not different between groups (0.06, P = 0.82). Conclusions Initiating chronic TIS therapy in the routine clinical care of patients with CF was associated with improvement in FEV1 % pred but no change in rate of decline, which means that this benefit was sustained over the 2 years studied. Pediatr Pulmonol. 2014; 49:529–536. © 2013 Wiley Periodicals, Inc.